Pengaruh kombinasi vitamin c dan vitamin e terhadap Kadar malondialdehid plasma pasien diabetes mellitus tipe 2 - Yasin, Yade Kurnia; Kartasurya, Martha Irene; RMD, RA Kisdjamiatun (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2015)
Background: Malondialdehyde (MDA) levels produced by oxidative stress in type 2 diabetes mellitus (T2DM) is higher than in non diabetes patients. Vitamin C and E inhibit oxidative stress and MDA production. The purpose of this study was to prove the effects of combined vitamin C and vitamin E on MDA plasma levels in T2DM patients.Methods: This double blind randomized pre post test control group design was carried out on 35 patients with T2DM without complication (age 40-60 yr) in Makassar. The treatment group (n=18) received vitamin C 250 mg/day plus vitamin E 400 IU/day and the control group (n=17) received placebo (seaweed powder 250 mg), for six weeks. Vitamin C was consumed before meal and vitamin E after meal. MDA levels were measured before and after supplementation by using TBARs method. Food intake and activity were derived from 24-hour recall method.Results: There was no different on MDA levels at baseline (p=0.151). At the end of the study, MDA levels increased in control group (5.8±2.74 to 7.2±3.00 nmol/ml; p=0.044) but not in the treatment group (7.2±2.88 to 7.7±2.02 nmol/ml; p=0.490). There was no difference in MDA alteration between the goups (p=0.316). There was no different in MDA levels at the end of the study (p=0.061) and confirmed after controlling the confounding variables: vitamin E intake and fasting blood glucose (p=0.809). Conclusion: Combined vitamin C 250 mg and vitamin E 400 IU for 6 weeks did not reduce MDA levels, but inhibit MDA production in T2DM patients.